Emerging Adulthood : Pengembangan Teori Erikson Mengenai Teori Psikososial Pada Abad 21 - Diana Putri Arini (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2021)
Abstract : Erik Erikson, a neo-psychoanalyst, developed the psychosocial stages of humans that became the reference for human development. One of the psychosocial stages is early adulthood which has the task of forming intimacy. Erikson does not explain the transition from adolescence to young adulthood which is full of conflicts between self-expectations and the demands of the times. Erikson's theory was further developed by Arnett (2000) because there were changes in the times which resulted in the task demands in young adulthood changing. Arnett proposed a new developmental stage, namely emerging adulthood, an extended adolescent transitional phase, ranging from 18-29 years of age.Arnett's theory is further expanded by Robbins and Wilner (2001) to find the phenomenon of quarter life crisis, a phenomenon of anxiety about the future by 20-year-old adolescents who form independence both financially and in romantic relationships. This article contains a review of the views of adulthood that emerged in the 20th century and the life of the quarter-life crisis that is currently being discussed. The research method used is literacy studies by looking for the last 10 years of research on emerging adulthood. The results of the literacy study report that changes in social norms and technological advances have changed the structure of society so as to produce a new stage, namely emerging adulthood. Emerging adulthood has various crisis conditions that occur when individuals complete their education. Keywords: Psychosocial Stage, Quarter Life Crisis, Emerging Adulthood Abstrak :Erik Erikson, seorang neo-psikoanalis, mengembangkan tahap psikososial manusia yang menjadi acuan bagi perkembangan manusia. Salah satu tahapan psikososial adalah masa dewasa awal yang memiliki tugas membentuk keintiman. Erikson tidak menjelaskan transisi masa remaja ke masa dewasa muda yang penuh dengan konflik antara ekspektasi diri dan tuntutan zaman. Teori Erikson dikembangkan lagi oleh Arnett (2000) karena ada perubahan zaman yang mengakibatkan tugas tuntutan di masa dewasa muda berubah. Arnett mengajukan tahapan perkembangan baru yaitu emerging adulthood, fase transisi remaja yang diperpanjang, berkisar antara usia 18-29 tahun. Teori Arnett diperluas lagi oleh Robbins dan Wilner (2001) menemukan fenomena quarter life crisis, fenomena kecemasan tentang masa depan oleh remaja berusia 20 tahun yang membentuk kemandirian baik secara finansial maupun dalam hubungan romantis. Artikel ini berisi menijau kembali pandangan masa dewasa yang muncul abad 20 serta kehidupan krisis seperempat kehidupan yang sedang marak diperbincangkan. Metode penelitian yang dilakukan menggunakan kajian literasi dengan mencari penelitian 10 tahun terakhir mengenai emerging adulthood. Hasil kajian literasi melaporkan perubahan norma sosial dan kemajuan teknologi telah mengubah struktur masyarakat sehingga menghasilkan satu tahapan baru yaitu emerging adulthood. Masa emerging adulthood memiliki berbagai kondisi krisis terjadi ketika individu menyelesaikan pendidikannya. Kata Kunci : Tahapan Psikososial, Krisis Kehidupanm Masa Dewasa